How processing may affect milk protein digestion and overall physiological outcomes: A systematic review. Issue 14 (5th August 2020) - van Lieshout, Glenn A. A.; Lambers, Tim T.; Bragt, Marjolijn C. E.; Hettinga, Kasper A.
Abstract: Dairy is one of the main sources for high quality protein in the human diet. Processing may, however, cause denaturation, aggregation, and chemical modifications of its amino acids, which may impact protein quality. This systematic review covers the effect of milk protein modifications as a result of heating, on protein digestion and its physiological impact. A total of 5363 records were retrieved through the Scopus database of which a total of 102 were included. Although the degree of modification highly depends on the exact processing conditions, heating of milk proteins can modify several amino acids. In vitro and animal studies demonstrate that glycation decreases protein digestibility, and hinders amino acid availability, especially for lysine. Other chemical modifications, including oxidation, racemization, dephosphorylation and cross-linking, are less well studied, but may also impact protein digestion, which may result in decreased amino acid bioavailability and functionality. On the other hand, protein denaturation does not affect overall digestibility, but can facilitate gastric hydrolysis, especially of β-lactoglobulin. Protein denaturation can also alter gastric emptying of the protein, consequently affecting digestive kinetics that can eventually result in different post-prandial plasma amino acid appearance. Apart from processing, the kinetics of protein digestion depend on the matrix in which the protein is heated. Altogether, protein modifications may be considered indicative for processing severity. Controlling dairy processing conditions can thus be a powerful way to preserve protein quality or to steer gastrointestinal digestion kinetics and subsequent release of amino acids. Related physiological consequences mainly point towards amino acid bioavailability and immunological consequences.